Sarcomas with RAD51B fusions are associated with a heterogeneous phenotype - Chang, Hsin-Yi; Dermawan, Josephine; Sharma, Aarti; Dickson, Brendan; Turashvili, Gulisa; Torrence, Dianne; Nucci, Marisa; Chiang, Sarah; Oliva, Esther; Kirchner, Martina; Stenzinger, Albrecht; Mechtersheimer, Gunhild; et al. (Modern pathology, 2024)
RAD51B-rearranged sarcomas are rare neoplasms that exhibit a heterogeneous morphology. To date, 6 cases have been reported, all involving the uterus, including 4 perivascular epithelioid cell tumors (PEComas) and 2 leiomyosarcomas (LMS). In this study, we describe the morphologic, immunohistochemical, and molecular features of 8 additional sarcomas with RAD51B rearrangement, including the first extrauterine example. All patients were women with a median age of 57 years at presentation. Seven tumors originated in the uterus, and one in the lower extremity soft tissue, with a median tumor size of 12 cm. Histologically, 4 tumors showed predominantly spindle cell morphology with eosinophilic fibrillary cytoplasm, with or without nuclear pleomorphism, whereas 2 tumors exhibited pleomorphic epithelioid cells, featuring clear to eosinophilic, granular cytoplasm. Two neoplasms exhibited undifferentiated cytomorphology, including one with uniform small blue round cells. All tumors showed high-grade cytologic atypia and high mitotic activity (median: 30/10 high-power fields), whereas coagulative necrosis was noted in 6 cases and lymphovascular invasion in 2. By immunohistochemistry, 2 showed myoid and melanocytic markers in keeping with PEComa, whereas 4 cases were only positive for smooth muscle markers consistent with LMS (including 3 myxoid). The remaining 2 cases had a nonspecific immunoprofile. Five cases tested by targeted RNA sequencing (Archer FusionPlex, Illumina TruSight) showed different fusion partners (HMGA2, PDDC1, and CEP170). RAD51B rearrangements were identified by FISH in the remaining 3 cases. Targeted DNA sequencing in 2 cases was negative for TSC gene alterations. Clinical outcome, available in 5 patients (median follow-up, 19 months), revealed 3 local recurrences, 2 lung metastases, and 4 deaths due to disease. Our results expand the spectrum of sarcomas with RAD51B fusions, demonstrating variable clinical presentations, morphologic spectrum, and fusion partners. These tumors have a predilection for a uterine location, with either LMS, PEComa, or undifferentiated phenotypes, and are associated with an aggressive clinical course.